Pelatihan Peer Counselor dan Pengenalan Media Promotif Untuk Peer Counselor - Resti Rahmadika Akbar; Rahma Triyana; Prima Adelin (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
Medical students as early adults have different challenges from high school, especially medical students. Based on the results of the previous study, it was found that medical students experienced anxiety, stress, and even depression with various levels. Ranging from mild to moderate-severe. Various efforts have been made, starting with increasing early detection of students from the first year, to the training stage to increase the role of academic advisory lecturers, to solving student problems that are sent to the counseling guidance section. The purpose of this training is that peer guidance services can be used as a form of guidance and counseling services provided to adolescents or early adults who have low social interaction. Before the training, it was started with the selection stage for peer counselors using an empathy questionnaire, based on the results of the questionnaire 28 students were found to be candidates for peer counselors. The training begins with a pretest then presentation material and case discussions then end with a post-test. Based on the results of the pre-test and post-test, there was an increase in knowledge about peer counselors, their roles, the benefits of counseling, and media that can be used as promotions as part of the peer counselor's duties. It is hoped that from this training, students can increase the role of assistance to students from the early stages so that severe cases experienced by students both in terms of academic and non-academic can be resolved.